2013
DOI: 10.1007/s10911-013-9301-9
|View full text |Cite
|
Sign up to set email alerts
|

Deconvoluting the Obesity and Breast Cancer Link: Secretome, Soil and Seed Interactions

Abstract: Obesity is associated with increased risk of breast cancer in postmenopausal women and is linked with poor prognosis in pre- and postmenopausal breast cancer patients. The mechanisms underlying the obesity-breast cancer connection are becoming increasingly clear and provide multiple opportunities for primary to tertiary prevention. Several obesity-related host factors can influence breast tumor initiation, progression and/or response to therapy, and these have been implicated as key contributors to the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…We found that a high level of nuclear pSmad2 in breast cancer cells was only associated with breast cancer outcome among nonobese breast cancer patients, suggesting that this measure cannot serve as a prognostic biomarker for overweight/obesity patients. This variation may be explained by obesity-related biological changes, such as increased hormone/growth factors (e.g., estrogens, insulin, insulin-like growth factor 1, leptin, adiponectin, and hepatocyte growth factor), as well as an increased level of inflammatory cytokines and vascular regulators (40), which may be dominant among obese individuals and mask the effects of the TGF-β pathway. Interestingly, we found that overexpression of nuclear pSmad2 in tumor cells was significantly associated with a favorable outcome in patients with earlier stages of breast cancer, as opposed to the later stages, and this association was seen only among persons with higher BMI (≥25).…”
Section: Discussionmentioning
confidence: 99%
“…We found that a high level of nuclear pSmad2 in breast cancer cells was only associated with breast cancer outcome among nonobese breast cancer patients, suggesting that this measure cannot serve as a prognostic biomarker for overweight/obesity patients. This variation may be explained by obesity-related biological changes, such as increased hormone/growth factors (e.g., estrogens, insulin, insulin-like growth factor 1, leptin, adiponectin, and hepatocyte growth factor), as well as an increased level of inflammatory cytokines and vascular regulators (40), which may be dominant among obese individuals and mask the effects of the TGF-β pathway. Interestingly, we found that overexpression of nuclear pSmad2 in tumor cells was significantly associated with a favorable outcome in patients with earlier stages of breast cancer, as opposed to the later stages, and this association was seen only among persons with higher BMI (≥25).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, increased adiposity has been positively associated with estrogen receptor-positive (ER+) breast cancer risk in post-menopausal women (6). Furthermore, numerous studies have described breast cancer-promoting effects of adipokines, predominantly those deregulated in obesity (7). However, few investigations have directly addressed the influence of mammary adipocyte-derived signals on triple-negative breast cancer (TNBC: tumors lacking ER, progesterone receptor and HER2 expression).…”
Section: Introductionmentioning
confidence: 99%
“…A number of mechanisms have been proposed to explain this obesity-breast cancer connection, including abnormalities in the circulating levels of estrogens, insulin, insulin-like growth factor, leptin, adiponectin, vascular regulators, and inflammatory cytokines [13]. However, exploration of these signaling molecules has thus far not produced any improvement in the treatment regimen for obese breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%